2015
DOI: 10.1371/journal.pntd.0003623
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Geographic Distribution of Nontuberculous Mycobacteria Clinical Isolates from Sputum Samples in the Eastern Region of China

Abstract: BackgroundNontuberculous mycobacteria (NTM) have been reported to be increasing worldwide and its geographic distribution differs by region. The aim of this study was to describe the epidemiology and distribution of NTM in the eastern part of China.MethodsSputum samples were collected from 30 surveillance sites for tuberculosis drug resistance test from May 1, 2008 to December 31, 2008. Identification was performed using a biochemical test, multiplex PCR and GenoType Mycobacterium CM/AS assay.ResultsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 30 publications
(35 reference statements)
5
30
0
1
Order By: Relevance
“…In many countries, MAC (including M. intracellulare and M. avium ) are the most common NTM isolates. On the other hand, M. avium is predominant in North- and South America, M. intracellulare is most frequently isolated in Australia-Queensland, South Africa and some provinces in China6202122. Our study showed that M. intracellulare was the most common species of NTM isolation, followed by M. abscessus in Beijing Chest Hospital which is located in north of China.…”
Section: Discussionmentioning
confidence: 58%
“…In many countries, MAC (including M. intracellulare and M. avium ) are the most common NTM isolates. On the other hand, M. avium is predominant in North- and South America, M. intracellulare is most frequently isolated in Australia-Queensland, South Africa and some provinces in China6202122. Our study showed that M. intracellulare was the most common species of NTM isolation, followed by M. abscessus in Beijing Chest Hospital which is located in north of China.…”
Section: Discussionmentioning
confidence: 58%
“…Although disseminated NTM disease is seen almost exclusively in immunosuppressed individuals, the vast majority of pulmonary NTM disease in the United States is due to Mycobacterium avium complex (MAC) and occurs in seemingly immunocompetent patients, disproportionately affecting females, older persons, and those with bronchiectasis or chronic obstructive lung disease (2)(3)(4)(5)(6)(7). Incidence rates are between 5/100,000 (general population) and 30/100,000 (.80 years old) patient-years, and are on the rise (6).…”
mentioning
confidence: 99%
“…In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent. In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high . This is likely also influential to the poor test concordance that we see in this study .…”
Section: Discussionmentioning
confidence: 47%
“…In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high. 35 This is likely also influential to the poor test concordance that we see in this study. 36 Although our results show a relationship between diabetes and QFT positivity, the same association is not present with diabetes and tuberculin positivity.…”
Section: Discussionmentioning
confidence: 85%